Pengaruh Takaran Mikoriza dan Jarak Tanam terhadap Pertumbuhan dan Hasil Kacang Tanah pada Lahan Gambut - Raka Ayu Riskitasari; Bakti Nur Ismuhajaroh; Bambang Fredrickus Langai (Jurusan Agronomi, Fakultas Pertanian, Universitas Lambung Mangkurat, 2026)
One strategy to increase peanut production is to apply effective cultivation technology, namely the use of biofertilizers and optimal planting distance management. This study aims to determine the effect of the interaction between mycorrhiza dosage and planting distance, to determine the effect of each single factor of mycorrhiza dosage and planting distance, and to determine the effect of mycorrhiza dosage and planting distance that shows the best peanut growth and yield on peatland. This study used a completely randomized factorial design with two factors: mycorrhiza (m) consisted of 4 levels m1 (0 kg ha-1), m2 (800 kg ha-1), m3 (1200 kg ha-1), and m4 (1600 kg ha-1), and planting distance (j) consisting of 4 levels j1 (40 × 10 cm), j2 (40 × 20 cm), j3 (40 × 30 cm), and j4 (40 × 40 cm). There were 16 treatment combinations repeated 3 times, resulting in 48 experimental units. The parameters observed were plant height (cm), number of branches, number of flowers, wet weight of canopy (g), dry weight of canopy (g), wet weight of roots (g), dry weight of roots (g), root volume (ml), root length (cm), number of roots, number of pods, number of empty pods, number of filled pods, number of seeds, seed weight per plant (g), and seed weight per plot (g). The interaction between mycorrhiza and planting distance had a significant effect on root wet weight, root volume, and root length. The single factor of mycorrhiza only had a significant effect on root length. The single factor of planting distance had a significant effect on plant height at 42 days after planting, number of branches at 42 days after planting, number of flowers at 42 days after planting, wet weight of canopy, dry weight of canopy, wet weight of roots, dry weight of roots, root volume, root length, number of roots, number of pods, number of empty pods, number of filled pods, number of seeds, seed weight per plant, and seed weight per plot. The optimal mycorrhiza rate was 800 kg ha⁻¹ (m²) and the optimal planting distance was 40 × 40 cm (j4).